TINGKAT PENGETAHUAN ANEMIA IBU HAMIL DAN KEPATUHAN KONSUMSI TABLET FE - Tendean, Angelia Friska; Sumampouw, Rachel Victoria Frisya; Ering, Cherol Nelson (Klabat Journal of Nursing, 2025)
Adherence to iron (Fe) tablet supplementation is one of the key preventive strategies for anemia, which is a common health problem during pregnancy. Knowing about anemia is a crucial part of supporting adherence of Fe tablet intake. This study aimed to identify the corellation between pregnant women’s knowledge about anemia and their adherence to consuming Fe tablets. A descriptive correlational design with a cross-sectional approach was applied in this study. This sample was involving 84 respondents chosen through consecutive sampling. Findings revealed that 74 respondents (88.1%) demonstrated good knowledge, while 43 respondents (51.2%) were non-compliant in taking Fe tablets. The Spearman rank correlation test produced r = 0.319 and p = 0.003 (< 0.05), indicating a weak but positive correlation between knowledge level and Fe tablet adherence among pregnant women at the Kolongan Public Health Center. It is suggested that the health center strengthen education and counseling for pregnant women through maternal classes and consistent monitoring to increase compliance with iron supplementation. Salah satu masalah kesehatan yang paling sering terhadi selama masa kehamilan adalah anemia. Menjaga kepatuhan ibu hamil terhadap penggunaan tablet besi adalah salah satu cara untuk mencegahnya. Pengetahuan tentang anemia sangat penting untuk mendukung kepatuhan ini. Tujuan dari penelitian ini adalah untuk mengevaluasi hubungan antara pengetahuan ibu hamil tentang anemia dan kepatuhan mereka terhadap penggunaan tablet besi. Penelitian ini menggunakan pendekatan deskriptif korelasional dan teknik cross-sectional, dengan 84 responden yang dipilih secara consecutive. Hasil studi menunjukkan bahwa 74 responden (88,1%) memiliki tingkat pengetahuan yang baik, sedangkan 43 responden (51,2%) tidak patuh mengonsumsi tablet Fe. Analisis Spearman rank memperoleh nilai r = 0,319 dan p = 0,003 (<0,05), membuktikan ada korelasi yang lemah tingkat pengetahuan dan kepatuhan mengonsumsi tablet Fe pada ibu hamil di wilayah kerja Puskesmas Kolongan. Disarankan agar Puskesmas Kolongan meningkatkan kegiatan edukasi dan pendampingan melalui kelas ibu hamil serta pemantauan rutin guna memastikan tablet Fe dikonsumsi oleh ibu